A chronology of Denmark's exchange-rate policy 1875-2003 - Kim Abildgren (Danmarks Nationalbank, 2004)
This paper offers a fact-oriented chronology of the Danish exchange-rate policy since the introduction of the krone as the Danish currency unit in 1875.
Keywords: E42; F31; F33; N23; N24; 330; Exchange-rate policy; Danish krone exchange rates; History of exchange rates; Gold Standard; Bretton Woods system; European exchange-rate co-operation; Wechselkurspolitik; Geschichte; Dänemark